Criticality and Film Music: Funny Games, Drive, and Meta-Textuality. Issue 2 (1st December 2022) - STOPFORD, RICHARD
Abstract : In this article, I argue that film music sometimes plays a 'critical' role. As such, my analysis seeks to extend writing on the philosophy of film, which tends to focus exclusively on its narrative and affective functions. I argue that 'criticality' occurs when the music plays a meta-textual role. That is, it directs audience attention away from the narrative and/or expressive dimensions of narrative, and towards the conventions and situation of cinema itself. This may make us think that critical film music is special to experimental cinema. I argue this is not the case. Through two examples of narrative movies, I argue that some kind of criticality is required to make sense of the music and, moreover, that narrative and/or expressive accounts of the music in these cases are, to some extent, unsatisfactory. Criticality is a distinctive role of music in narrative cinema.